1998
DOI: 10.1111/j.2042-3306.1998.tb05119.x
|View full text |Cite
|
Sign up to set email alerts
|

Onychomycosis in white line disease in horses: pathology, mycology and clinical features

Abstract: Summary This paper describes onychomycosis in horses and reports the pathological findings, associated fungi and incidence of concurrent white line disease. In addition to these observations, relevance between post mortem and clinical findings of onychomycosis are discussed in 3 necropsied horses. Samples were collected from 100 hooves from a total of 51 Thoroughbreds suffering from white line disease. Of these, 15 hooves from 13 horses were also complicated with severe hoof wall fissure formation. Preparation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 9 publications
0
8
0
1
Order By: Relevance
“…There is little information available about eumycotic mycetoma formation related to Scedosporium species. Scedosporium infection in other animal species has been documented including cats, horses, layer pullets, cows, and humans . In dogs, Scedosporium species have been previously documented causing keratomycosis, discospondylitis, osteomyelitis, disseminated disease, and rhinitis .…”
Section: Discussionmentioning
confidence: 99%
“…There is little information available about eumycotic mycetoma formation related to Scedosporium species. Scedosporium infection in other animal species has been documented including cats, horses, layer pullets, cows, and humans . In dogs, Scedosporium species have been previously documented causing keratomycosis, discospondylitis, osteomyelitis, disseminated disease, and rhinitis .…”
Section: Discussionmentioning
confidence: 99%
“…Poor hoof horn quality is therefore a major cause of reduced performance and lameness. Equine onychomycosis has become a recognised cause of poor horn quality and hoof horn disease 4–8 . Recent research 13,14 has confirmed that both dermatophytes, which are well known to infect skin and associated structures in humans and other species, and moulds exhibit keratinopathogenic activity.…”
Section: Discussionmentioning
confidence: 99%
“…In the last two decades, fungal infection has been associated with poor quality hooves and several hoof diseases 4–8 . The horn defects in horses suffering from equine onychomycosis range from brittle hooves with sand cracks, horn fissures and large crumbling areas around the nail holes 4,7,8 to severe cases of white line disease 5,6 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many direct or supporting lines of evidence have indicated that possible contributors to the formation of the Gidoh include decreasing toughness of the wall based on abnormal anatomical conformation of the foot [2, 18], swelling and softening of the horny structure by water and/or urine [6,7,8,9, 19], neglect of incipient lesions relating to irregular farriery [2], and infection of the wall by microorganisms [1, 2, 4, 5, 12, 13, 15,16,17, 19]. Scientific research data have shown that keratinopathogenic fungi can invade into, and proliferate in, horny structures of the foot [1, 15, 17]. This can result in the collapse of the hoof capsule due to the production of keratolytic enzymes [1, 12].…”
mentioning
confidence: 99%